Fast and Sensitive Detection of Anti-SARS-CoV-2 IgG Using SiO2@Au@CDs Nanoparticle-Based Lateral Flow Immunoassay Strip Coupled with Miniaturized Fluorimeter - Rui Wang; Junping Xue; Guo Wei; Yimeng Zhang; Chuanliang Wang; Jinhua Li; Xuhui Geng; Abbas Ostovan; Lingxin Chen; Zhihua Song (Biomolecules)
The development of a novel strategy for the measurement of SARS-CoV-2 IgG antibodies is of vital significance for COVID-19 diagnosis and effect of vaccination evaluation. In this investigation, an SiO2@Au@CDs nanoparticle (NP)-based lateral flow immunoassay (LFIA) strip was fabricated and coupled with a miniaturized fluorimeter. The morphology features and particle sizes of the SiO2@Au@CDs NPs were characterized carefully, and the results indicated that the materials possess monodisperse, uniform, and spherical structures. Finally, this system was employed for SARS-CoV-2 IgG antibody test. In this work, the strategy for the SARS-CoV-2 IgG antibody test possesses several merits, such as speed (less than 15 min), high sensitivity (1.2 × 10−7 mg/mL), broad linearity range (7.4 × 10−7~7.4 × 10−4 mg/mL), accurate results, high selectivity, good stability, and low cost. Additionally, future trends in LFAs using quantum dot-based diagnostics are envisioned.